2021
DOI: 10.3390/jcm10245894
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Psoriasis and Hidradenitis Suppurativa in Pregnancy, a Systematic Review

Abstract: Psoriasis and hidradenitis suppurativa (HS) are chronic inflammatory skin diseases that frequently develop in young women. The aim of this study is to evaluate how hidradenitis suppurativa and psoriasis impact women desiring to conceive, and their influence on fertility and gestation. A systematic review of articles dating from January 2015 to April 2021 was performed using the Scopus (Elsevier) database. The search terms were (psoriasis and (birth or pregnancy or fertility)) and ((hidradenitis suppurativa or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…Moreover, the rate of adverse effects of acitretin treatment is shown to be low, and they are not a cause for discontinuing treatment. This fact makes it a treatment with potential application, except in women of childbearing age with unsatisfied reproductive desires [28, 29].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the rate of adverse effects of acitretin treatment is shown to be low, and they are not a cause for discontinuing treatment. This fact makes it a treatment with potential application, except in women of childbearing age with unsatisfied reproductive desires [28, 29].…”
Section: Discussionmentioning
confidence: 99%
“…However, an individualized risk benefit discussion should be had with patients regarding treatment ( 67 ). Pregnancy in HS is a sensitive topic and should be approached with the patient with caution, as HS can lead to decreased fertility, and adverse reactions during pregnancy, as well as gestation triggering a clinical worsening of the disease ( 68 ). Therefore, biologic treatments in pregnancy should be discussed with patients of childbearing potential.…”
Section: What Concerns Should Gps Have During Biologic Usage?mentioning
confidence: 99%
“…Physiological changes during pregnancy may have a variable impact on HS course [ 142 ]. A recent systematic review and meta-analysis (including 8 studies [ 53 , 143 , 144 , 145 , 146 , 147 , 148 , 149 ], 672 pregnancy cases and 164 postpartum cases) found that the patient-reported rates of HS improvement and HS disease worsening were 0.24 and 0.20, respectively.…”
Section: Hs and Pregnancymentioning
confidence: 99%